Interrupted time series analysis of the impact of the COVID-19 pandemic and compulsory social health insurance system on fertility rates: a study of live births in Kazakhstan, 2019–2023 - Karibayeva, Indira; Moiynbayeva, Sharapat; Akhmetov, Valikhan; Yerkenova, Sandugash; Shaikova, Kuralay; Moshkalova, Gaukhar; Mussayeva, Dina; Tarakova, Bibinur (Frontiers in Public Health, 2024)
The COVID-19 pandemic triggered global health crises, affecting population health directly through infections and fatalities, and indirectly by increasing the burden of chronic diseases due to disrupted healthcare access and altered lifestyle behaviors. Amidst these challenges, concerns regarding reproductive health and fertility rates have emerged, necessitating an understanding of their implications for policymaking and healthcare planning. Furthermore, Kazakhstan's healthcare landscape underwent significant changes with the reintroduction of compulsory social health insurance system in January 2020, coinciding with the onset of the COVID-19 pandemic. This study aims to assess the impact of the COVID-19 pandemic and compulsory social health insurance system on fertility rates in Kazakhstan by examining live birth data from 2019 to 2024. Using Interrupted Time Series analysis, we evaluated the effect of the COVID-19 lockdown announcement and compulsory social health insurance system implementation on monthly birth rates, adjusted for the number of women of reproductive age from January 2019 to December 2023. In the final model, the coefficients were as follows: the effect of the COVID-19 lockdown was estimated at 469 (SE = 2600, p = 0.8576); the centering variable was estimated at 318 (SE = 222, p = 0.1573), suggesting no significant trend in monthly birth rates over time; the insurance effect was estimated at 7,050 (SE = 2,530, p < 0.01); and the effect of the number of women of reproductive age was estimated at -0.204 (SE = 0.0831, p = 0.01). The implementation of the compulsory social health insurance system, rather than the announcement of the COVID-19 lockdown, has had a significant positive impact on live birth rates in Kazakhstan. However, despite governmental efforts, live birth rates are declining, potentially due to unaddressed health needs of fertile women and economic challenges. Urgent policy-level actions are needed to address gaps in healthcare services and promote reproductive health.